2011
DOI: 10.1128/jvi.01813-10
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Respiratory Syncytial Virus Fusion Protein in the Fully Cleaved, Pretriggered State Is Triggered by Exposure to Low-Molarity Buffer

Abstract: The paramyxovirus fusion (F) glycoprotein is anchored in the virion membrane in a metastable, pretriggered form. Once triggered, the F protein undergoes a dramatic conformational extension that inserts its hydrophobic fusion peptide into the target cell membrane, then folds back on itself to bring the membranes together and initiate fusion. Unlike most other paramyxoviruses, the respiratory syncytial virus (RSV) F protein alone is sufficient to mediate membrane fusion and virus infection. To study the triggeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 46 publications
4
70
0
1
Order By: Relevance
“…This attachment protein-independent fusion activation has been well characterized in human RSV, bovine RSV, and ovine RSV (14)(15)(16). Recently, it was found that the F proteins of hMPV and aMPV also induce fusion without their attachment G proteins (17)(18)(19)(20), suggesting that the G protein is dispensable for attachment and fusion.…”
Section: H Uman Metapneumovirus (Hmpv) Is a Member Of The Genusmentioning
confidence: 98%
See 1 more Smart Citation
“…This attachment protein-independent fusion activation has been well characterized in human RSV, bovine RSV, and ovine RSV (14)(15)(16). Recently, it was found that the F proteins of hMPV and aMPV also induce fusion without their attachment G proteins (17)(18)(19)(20), suggesting that the G protein is dispensable for attachment and fusion.…”
Section: H Uman Metapneumovirus (Hmpv) Is a Member Of The Genusmentioning
confidence: 98%
“…Another unique characteristic of hMPV entry is that fusion of some hMPV strains requires low pH, whereas fusion of all other paramyxoviruses occurs at neutral pH (17,18,22). In addition, fusion of hMPV in cell culture requires the addition of exogenous protease (17,18), unlike the F protein of RSV but similar to the F proteins of some of the members of the Paramyxovirinae, such as Sendai virus, parainfluenza virus type 1, and avirulent strains of Newcastle disease virus (16). Together these results suggest that hMPV fusion is characterized by a unique combination of features making it distinct from other paramyxoviruses.…”
Section: H Uman Metapneumovirus (Hmpv) Is a Member Of The Genusmentioning
confidence: 99%
“…The differences may be explained by the distinct viral entry mechanisms. Unlike influenza virus, vesicular stomatitis virus, or Newcastle disease virus, RSV fusion does not require endosomal maturation and acidification (41,42), which in turn is a necessary step for endosomal TLR function. Therefore, the ssRNA genome may not be accessible to TLR7 upon RSV entry of human pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…This deposited fragment contains the motavizumab epitope and, according to the description in the Protein Data Bank (PDB), was derived as a by-product of cellular protease cleavage at some time during expression or purification. An alternate 30-kDa by-product corresponding to the remaining C terminus of F 1 (as determined by Western blotting to a C-terminally bound purification tag) has also been observed by other investigators during recombinant F protein expression (17). This product is absent in the cleavage-deficient mutations (E82A, L83A, V90A, and L93A) and reduced in others (Y86A and L96A).…”
Section: Resultsmentioning
confidence: 81%
“…This transition is irreversible under physiological conditions and renders the fusion protein inactive. Heat, low-molarity buffer, and freeze-thaw cycles have all been shown to cause this unidirectional conformation change (17,19,20). Recently, a number of conformation-specific antibodies have been characterized.…”
Section: Fig 2 Expression and Processing Of Hrc Mutations Transientlmentioning
confidence: 99%